RETRACTED ARTICLE: Consequences of health risk assessment of wastewater irrigation in Pakistan. Issue 7 (14th September 2019) - Sabeen, Maria; Mahmood, Qaisar; Ebadi, Abdol Ghaffar; Bhatti, Zulfiqar Ahmad; Faridullah,; Irshad, Muhammad; Kakar, Allauddin; Bilal, Muhammad; Arshad, Hafiz Muhammad; Shahid, Naeem
Statement of Retraction: We, the Editors and Publisher of Toxicological & Environmental Chemistry, have retracted the following article: Maria Sabeen, Qaisar Mahmood, Abdol Ghaffar Ebadi, Zulfiqar Ahmad Bhatti, Faridullah, Muhammad Irshad, Allauddin Kakar, Muhammad Bilal, Hafiz Muhammad Arshad and Naeem Shahid, 'Consequences of health risk assessment of wastewater irrigation in Pakistan Israel Affairs', Toxicological & Environmental Chemistry, 2019, DOI: 10.1080/02772248.2019.1619335 The article is retracted due to the oversights that were made during peer review process that resulted in the article being published online in error. Further review from independent reviewers was sought. This confirmed that the central findings and methodology of the study in question are unreliable and therefore unsuitable for publication. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".